Changes in the territorial distribution of population and job seekers with higher education in Hungary - Győri, Tímea (Studia Mundi – Economica, 2021)
The study uses different statistical methods to examine the change in the territorial distribution and concentration of the tertiary-educated population and the unemployed between 2001 and 2019. Among the known regional inequality indicators measuring regional disparities, the Dual index and the Hoover index were used. With the help of the location quotient (LQ), the representation of those with higher education in relation to the average was explored and represented at the settlement level. Territorial autocorrelation was performed to more complexly examine the distribution and concentration of tertiary graduates within the population and the unemployed. Spatial neighborhood impact was analyzed using the Global and Local Moran Index. The autocorrelation confirmed regular spatial arrangements in the spatial distribution of tertiary graduates. The study explores whether different weighting of raw data affects the result of autocorrelation, furthermore determines the differences between the location quotient and the GIS representation of Local Moran I.